Performing a catalysis reaction on filter paper: development of a metal palladium nanoparticle-based catalyst. Issue 1 (19th September 2018) - Zhao, Yili; Liu, Lei; Shi, Daniel; Shi, Xiangyang; Shen, Mingwu
Abstract : Palladium nanoparticles can be facilely immobilized onto filter paper via mediation by polyethylenimine for high-performance catalytic applications. Abstract : We report the polyethylenimine (PEI)-mediated immobilization of palladium nanoparticles (Pd NPs) onto filter paper for catalytic applications. In this work, filter paper was first assembled with PEI via electrostatic interaction, and the PEI-assembled filter paper was then complexed with PdCl4 2− ions, followed by sodium borohydride reduction to generate Pd NP-immobilized filter paper. Transmission electron microscopy reveals that Pd NPs have a diameter of 3 nm and are capable of being immobilized onto the filter paper. The Pd NP-immobilized filter paper exhibits remarkable catalytic activity and is reusable in the reductive transformation of Cr(vi ) to Cr(iii ) and 4-nitrophenol to 4-aminophenol. The strategy used to develop Pd NP-immobilized filter paper could be adopted to generate other metal NP-immobilized filter papers for other applications such as sensing materials, energy, environmental remediation, and biomedical sciences.